2021
DOI: 10.15561/20755279.2021.0107
|View full text |Cite
|
Sign up to set email alerts
|

Home quarantine - based rhythmic exercises: new fitness assessment and intervention in teaching physical education

Abstract: Background and Study Aim. The COVID – 19 pandemic has post threats on the physical and mental fitness of the people. Thus, the study determined the effectiveness of home quarantine - based rhythmic exercises to the fitness level of the university students in physical education. Material and Methods. University students were the participants of the study. 200 student populations who were taking physical education subject in the year 2020 were considered. Quasi – experimental research design was employed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…All students can also be recommended to use rhythmic exercises as homework. This coincides with the data of Garcia and Custodio [27], which showed the effectiveness of using rhythmic exercises in quarantine conditions. We also recommend that all students improve their knowledge in the field of sports education.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All students can also be recommended to use rhythmic exercises as homework. This coincides with the data of Garcia and Custodio [27], which showed the effectiveness of using rhythmic exercises in quarantine conditions. We also recommend that all students improve their knowledge in the field of sports education.…”
Section: Discussionsupporting
confidence: 91%
“…For this, it is relevant to determine whether the chosen specialty for study affects psychophysiological indicators and orthostatic reactions (i.e., reactions to a change in body position from horizontal to vertical). Also, determining the impact of lifestyle, in particular, sports, on indicators of psychophysiological functions and orthostatic reactions [27,28] is also an urgent task. Based on the above, the hypothesis was put forward in the study: 1 -there is a relationship between the specialty chosen by students for professional improvement and indicators of psychophysiological functions and orthostatic reactions; 2practicing any kind of sport has a positive effect on psychophysiological indicators and the state of vascular tone regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Current researches [1,30] demonstrated that physical activity levels decrease during quarantine consist of higher sitting time at home. Previous studies presented that student might home-based activity during home confinement such as active short breaks, walking around the house, and self-paced exercise [31,32]. Therefore, when the daily behaviour of people changes some restrictions, psychological factors might affect physiological and metabolically factors consist of poor sleep quality and MSP pain.…”
Section: Discussionmentioning
confidence: 99%
“…It states that it is a systematic planning process based on practical experience and sports science knowledge of structuring (long-term) training according to a training objective and individual level of performance. As a result, the development of the various training programs can be designed as a coaching program, a collective or individual program, over several years or annually, over a long cycle or on a training unit [35,36,37,38]. In addition, the individual training program contains the fundamental guidelines that will allow you to achieve optimal performance.…”
Section: Discussionmentioning
confidence: 99%